2013
DOI: 10.1002/j.0022-0337.2013.77.9.tb05595.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes about HIV/AIDS of Students in H.P. Government Dental College and Hospital, Shimla, India

Abstract: The purpose of this cross-sectional survey was to assess the knowledge and attitudes towards patients with HIV/AIDS among dental students in H.P. Government Dental College, Shimla, India. In November 2011, a survey was conducted of all the dental students of the college using a forty-ive-item, self-administered questionnaire. The total mean knowledge score was 68.3 percent (good knowledge). The mean knowledge score was statistically higher in the clinical group than in the preclinical group. A majority of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 26 publications
7
20
0
1
Order By: Relevance
“…In the current study, the knowledge regarding Oral Manifestations associated with the HIV/AIDS was adequate such as Oral candidiasis (95.0%), Oral Hairy leukoplakia (85.0%), Necrotizing ulcerative gingivitis (88.0%), Herpes Zoster (81.0%), Kaposi's sarcoma (86.0%), Apthous ulcers (81.0%) and Salivary Gland disease (75.0%) which was similar to the study conducted by Sadeghi and Hakimi among Iranian dental students [ 45 ], in which, 98.1% respondents correctly identified oral candidiasis, 95.8% identified Major Aphthous, and 93.8% identified Kaposi's sarcoma. This was also similar to the study conducted by Crossley [ 38 ] among dentists working within the South Cheshire region, UK in which, 96% correctly identified Kaposi's sarcoma, 87% identified Oral candidiasis, 70% identified Acute ulcerative gingivitis, 73% identified Hairy leukoplakia and 67% identified Herpetic infections and Fotedar et al [ 18 ], more than 73 percent of the dental students in the H. P. Government Dental College and Hospital, Shimla, India knew about the lesions strongly associated with HIV/AIDS such as Kaposi sarcoma, hairy leukoplakia, and oral candidiasis.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In the current study, the knowledge regarding Oral Manifestations associated with the HIV/AIDS was adequate such as Oral candidiasis (95.0%), Oral Hairy leukoplakia (85.0%), Necrotizing ulcerative gingivitis (88.0%), Herpes Zoster (81.0%), Kaposi's sarcoma (86.0%), Apthous ulcers (81.0%) and Salivary Gland disease (75.0%) which was similar to the study conducted by Sadeghi and Hakimi among Iranian dental students [ 45 ], in which, 98.1% respondents correctly identified oral candidiasis, 95.8% identified Major Aphthous, and 93.8% identified Kaposi's sarcoma. This was also similar to the study conducted by Crossley [ 38 ] among dentists working within the South Cheshire region, UK in which, 96% correctly identified Kaposi's sarcoma, 87% identified Oral candidiasis, 70% identified Acute ulcerative gingivitis, 73% identified Hairy leukoplakia and 67% identified Herpetic infections and Fotedar et al [ 18 ], more than 73 percent of the dental students in the H. P. Government Dental College and Hospital, Shimla, India knew about the lesions strongly associated with HIV/AIDS such as Kaposi sarcoma, hairy leukoplakia, and oral candidiasis.…”
Section: Discussionsupporting
confidence: 87%
“…The Questionnaire used for the study was a structured Questionnaire which contained questions pertaining to the knowledge and attitude of the faculty members. The questionnaire was formulated after the review of other questionnaires used in the literature by Aggarwal and Panat [ 17 ], Fotedar et al [ 18 ] and Manz et al [ 19 ] for the assessment of knowledge and attitude among the dental practitioners and dental students. The attitude related questions assessed the willingness of the faculty members towards the dental treatment of HIV/AIDS patients, the potential barriers they perceived and infection control procedures in the treatment of the HIV/AIDS patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are similar to a studies done among students from Government College in Chandigarh, India, among medical students from costal Karnataka, India and among dental students from Shimla, India. [5][6][7] Similar results were seen among students from Peshawar University, Pakistan. 8 Knowledge and attitude scores reported in our study are better than those reported in studies from Nepal and UAE.…”
Section: Discussionsupporting
confidence: 67%